2014
DOI: 10.1007/978-3-662-45504-3_32
|View full text |Cite
|
Sign up to set email alerts
|

Representation and Analysis of Piecewise Linear Functions in Abs-Normal Form

Abstract: International audienceIt follows from the well known min/max representation given by Scholtes in his recent Springer book, that all piecewise linear continuous functions $$y = F(x) : \mathbb {R}^n \rightarrow \mathbb {R}^m$$ can be written in a so-called abs-normal form. This means in particular, that all nonsmoothness is encapsulated in $$s$$ absolute value functions that are applied to intermediate switching variables $$z_i$$ for $$i=1, \ldots ,s$$. The relation between the vectors $$x, z$$, and $$y$$ is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Adjoint models have been common in oceanic and atmospheric contexts (Talagrand and Courtier, 1987;Thacker and Long, 1988;Errico and Vukicevic, 1992) for decades. The method's popularity has been increasing steadily.…”
Section: Formal Reverse Mode Of Admentioning
confidence: 99%
“…Adjoint models have been common in oceanic and atmospheric contexts (Talagrand and Courtier, 1987;Thacker and Long, 1988;Errico and Vukicevic, 1992) for decades. The method's popularity has been increasing steadily.…”
Section: Formal Reverse Mode Of Admentioning
confidence: 99%
“…Each inner iteration of the method requires the solution of a piecewise linear system, e.g. by the solvers proposed in [Rad16,SGRB14,GBRS15]. We intend to deliver an efficient implementation for an integrated framework of piecewise linearization and ODE as well as equation solving in subsequent publications.…”
Section: Final Remarksmentioning
confidence: 99%
“…Streubel et al considered functions Δ y =Δ F ( x ,Δ x ), normalΔFfalse(·,·false):double-struckRn×double-struckRndouble-struckRm, that are piecewise linear with respect to the second argument normalΔxdouble-struckRn. It was also shown that these functions can be used to approximate any abs‐factorable function y = F ( x ), F:double-struckRndouble-struckRm, at a fixed base point xdouble-struckRn for variable directional increment normalΔxdouble-struckRn and satisfy locally ‖‖Ffalse(x+normalΔxfalse)Ffalse(xfalse)normalΔFfalse(x;normalΔxfalse)γfalse‖normalΔxfalse‖2,1em0<γdouble-struckR. …”
Section: Introductionmentioning
confidence: 99%
“…Streubel et al 1 considered functions Δy = ΔF(x, Δx), ΔF(·, ·) ∶ R n × R n → R m , that are piecewise linear with respect to the second argument Δx ∈ R n . It was also shown 2 that these functions can be used to approximate any abs-factorable function y = F(x), F ∶ R n → R m , at a fixed base point x ∈ R n for variable directional increment Δx ∈ R n and satisfy locally ‖F(x + Δx) − F(x) − ΔF(x; Δx)‖ ≤ ||Δx|| 2 , 0 < ∈ R. (1) Moreover, it was observed 3 that the piecewise linear approximations ΔF contain valuable information about the nonsmoothness of the underlying function F and allow for a compact algebraic representation, which will be called abs-normal form (ANF) in the following. Namely, the piecewise linear approximations ΔF can be represented by the set of piecewise affine equations…”
Section: Introductionmentioning
confidence: 99%